Pengaruh Persepsi Kemudahan,Persepsi Manfaat ,Risiko, Return, Social Influence Terhadap Penggunaan Aplikasi Reksa Dana Bibit - Fauzan; Renggo Bawani Wijayaningrum (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of perceived ease of use, perceived benefits, risks, return, and social influence on the use of the Bibit mutual fund application at Universitas Muhammadiyah Surakarta. The research method used is a quantitative descriptive method with an associative approach, using primary data obtained through questionnaires. The data were analyzed using SPSS version 25, with validity, reliability, classical assumptions tests, and multiple linear regression analysis. The results show that perceived ease of use, benefits, risks, return, and social influence significantly and positively affect the use of the application. This study recommends developers to continuously improve the app’s features and leverage social influence. The limitation of this study is the limited sample and the use of secondary data.